Postscript to the Dapu of Letian Cao - Yang, Chunhui; Cui, Xiangzhe (Journal of Educational Research and Policies, 2025)
Dapu, as an act of interpretative reconstruction of historical music scores, is both a creative endeavor and a practice of rendering sound from notation. Throughout the dapu process, one must synthesize multifaceted elements—such as the historical context of the composition, the musical background, the characteristics of the score versions, and the thematic essence of the piece—to meticulously reconstruct the composer’s original intentions and thereby manifest the work’s musical form. Letian Cao (Ode to Joyful Heaven) is preserved in A Primer to Qin Studies (1894), a Qing-dynasty guqin treatise published in the 20th year of the Guangxu reign. This essay comprises two sections: the first examines the historical and cultural context of Letian Cao; the second documents the practical procedures of its dapu and highlights the distinctive techniques derived from the Guangling School employed during the reconstruction.